1997
DOI: 10.1111/j.1744-7429.1997.tb00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Biology of the Monoecious Understory Palm Prestoea schultzeana in Amazonian Ecuador1

Abstract: Prestoea schultzeana is a monoecious, protandrous palm in the forest understory of Amazonian Ecuador. We studied its leaf production, population density, sexual expression, phenology, pollination, and the specificity of the floral visitors. On average, 1.4 leaves and 0.9 inflorescences are produced per individual per year. The number of staminate flowers per inflorescence is relatively constant compared with the number of pistillate flowers which varies greatly. Flowering occurs in staminate and pistillate pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
6

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 6 publications
2
41
0
6
Order By: Relevance
“…Females forage on flowers to collect nectar and pollen, which is necessary for larval development. In Mexico and Panama, Megalopta uses many plant species for pollen (Gonzalez et al 2010a;Tierney et al 2012), which have both diurnal and nocturnal anthesis (Falcão et al 1992;Ervik & Feil 1997;Hopkins et al 2000;Gressler et al 2006;Oliveira et al 2009), during either the dry or wet season (Wcislo et al 2004). Given the similar seasonal pattern of Megalopta observed in this study in comparison with that recorded in Central America (Wolda & Roubik 1986), we assume that the attractiveness of bait traps might be related to the fragrance produced by the flowers that produce nectar, pollen or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Females forage on flowers to collect nectar and pollen, which is necessary for larval development. In Mexico and Panama, Megalopta uses many plant species for pollen (Gonzalez et al 2010a;Tierney et al 2012), which have both diurnal and nocturnal anthesis (Falcão et al 1992;Ervik & Feil 1997;Hopkins et al 2000;Gressler et al 2006;Oliveira et al 2009), during either the dry or wet season (Wcislo et al 2004). Given the similar seasonal pattern of Megalopta observed in this study in comparison with that recorded in Central America (Wolda & Roubik 1986), we assume that the attractiveness of bait traps might be related to the fragrance produced by the flowers that produce nectar, pollen or both.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that only females have been captured in the orchid bee baits suggests that they use olfactory clues to search for pollen during dim-light conditions. Some species of plants used by dim light bees that also produce scents are Prestoea schultzeana (Arecaceae), Parkia velutina (Fabaceae), and Ternstroemia dentata (Theaceae) (Ervik & Feil 1997;Melo 1995;Hopkins et al 2000). If this is correct, the olfactory system may have also played as important a role in the evolution of Megalopta as the visual system (Greiner et al , 2005Kelber et al 2005;Warrant 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Foi possível verifi car uma assincronia signifi cativa na abertura entre os tipos de fl ores, estaminadas e pistiladas, na mesma infl orescência (X2 Î ± 0,05,GL15 = 20712,311; P < 0,0001). Alguns estudos realizados com palmeiras de outros gêneros em diferentes regiões têm demonstrado que as fl ores das fases estaminadas e pistiladas, em geral, não apresentam sobreposição na sua abertura, como observado em Prestoea schultzeana (Burret) H. E. Moore, no Equador (Ervik & Feil 1997) e Cocos nucifera L., no México (Ramirez et al 2004).…”
Section: Resultsunclassified
“…Da mesma maneira, a anemofi lia foi excluída para a palmeira Mauritia fl exuosa, única espécie da família que ocorre em veredas (Abreu 2001). Ervik & Feil (1997), em estudo com a palmeira Prestoea schultzeana, também excluíram a possibilidade de sua polinização pelo vento, pois além do ambiente de estudo não facilitar a circulação do ar, as fl ores não possuem superfícies estigmáticas apropriadas para receber pólen transportado pelo vento.…”
Section: Resultsunclassified
“…Studies of the reproductive biology of palms have revealed a wide range of plant adaptations that match the behavioural characteristics of their pollinators (Henderson 1986, Zona 1987, Andersson et al 1988, Herrera 1989, Olesen & Balslev 1990, Barfod 1991, Búrquez et al 1987, Scariot et al 1991, Listabarth 1992, Borchsenius 1993, Ervik 1993, Bernal & Ervik 1996, Bøgh 1996, Listabarth 1996, Ervik & Feil 1997, Küchmeister et al 1997, Anstett 1999, Howard et al 2001. The most common pollen dispersing agents are beetles followed by bees and flies.…”
Section: Introductionmentioning
confidence: 99%